2023
DOI: 10.1152/japplphysiol.00411.2023
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to 9 hours of heat exposure in young and older adults. Part II: Autophagy and the acute cellular stress response

Abstract: With rising global temperatures, heat-related mortality is increasing, particularly among older adults. While this is often attributed to declines in thermoregulatory function, little is known regarding the effect of age on the cellular processes associated with mitigating heat-induced cytotoxicity. We compared key components of the cellular stress response in 19 young (19-31 years; 10 female) and 37 older adults (61-78 years; 10 female) during 9 hours of heat exposure (40°C, 9% relative humidity). Mean body t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Supporting this postulate, we recently observed that although type 2 diabetes is associated with reduced heat loss during moderate exercise in the heat, 96 physiological responses did not differ between older adults with or without well-controlled type 2 diabetes during a resting 3-h exposure to 44°C and 35% relative humidity 97 conditions exceeding those measured indoors during heat waves. 20 , 21 , 34 Likewise, we recently showed no differences in body temperature 98 or cellular strain 99 between older adults with and without well-controlled type 2 diabetes and/or hypertension during 9-h of exposure to 40°C, 9% relative humidity. Furthermore, although maintaining high levels of aerobic fitness has been shown to prevent the age-related decline in thermoregulatory function during exercise heat-stress, these effects are considerably reduced at lower levels of heat stress like those that might be experienced by vulnerable groups indoors during hot weather.…”
Section: Discussionmentioning
confidence: 89%
“…Supporting this postulate, we recently observed that although type 2 diabetes is associated with reduced heat loss during moderate exercise in the heat, 96 physiological responses did not differ between older adults with or without well-controlled type 2 diabetes during a resting 3-h exposure to 44°C and 35% relative humidity 97 conditions exceeding those measured indoors during heat waves. 20 , 21 , 34 Likewise, we recently showed no differences in body temperature 98 or cellular strain 99 between older adults with and without well-controlled type 2 diabetes and/or hypertension during 9-h of exposure to 40°C, 9% relative humidity. Furthermore, although maintaining high levels of aerobic fitness has been shown to prevent the age-related decline in thermoregulatory function during exercise heat-stress, these effects are considerably reduced at lower levels of heat stress like those that might be experienced by vulnerable groups indoors during hot weather.…”
Section: Discussionmentioning
confidence: 89%